Quantitative Evaluation of Soil Functions: Potential and State - Vogel, Hans-Jörg; Eberhardt, Einar; Franko, Uwe; Lang, Birgit; Ließ, Mareike; Weller, Ulrich; Wiesmeier, Martin; Wollschläger, Ute (Frontiers in Environmental Science, 2019)
Soils play a key role for the functioning of terrestrial ecosystems. Thus, soils are essential for human society not only because they form the basis for the production of food. This has been recognized since long and during the last three decades the need to establish methods to evaluate the ability of soils to provide soil functions has moved towards the top of the agenda in soil science. Quantitative evaluation schemes are indispensable to adequately include soils into strategies to reach sustainable development targets. In this paper we build upon existing approaches and propose a concept to evaluate individual soil functions with respect to the soil’s natural potential in contrast to its actual state. This leads to a separation of indicator variables and allows for conclusions on the structure of appropriate models that are required to predict the dynamics of soil functions in response to external perturbation. This concept is demonstrated for the production function, carbon storage and water storage which are evaluated exemplarily for different plots of a long-term field experiment. It is discussed for nutrient cycling and the habitat function where evaluation schemes are still less obvious.